Pediatric sample inclusion in an opt-out biorepository linking DNA to de-identified medical records: Pediatric BioVU - McGregor, Tracy L. (2012)
The Vanderbilt DNA repository, BioVU, links DNA from leftover clinical blood samples to de-identified electronic medical records. After initiating adult sample collection, pediatric extension required consideration of ethical concerns specific to pediatrics and implementation of specialized DNA extraction methods. In the first year of pediatric sample collection, over 11,000 samples were included from individuals younger than 18 years. We compared the pediatric BioVU cohort to the overall Vanderbilt University Medical Center pediatric population and found similar demographic characteristics; however, the BioVU cohort has higher rates of select diseases, medication exposures, and laboratory testing, demonstrating enriched representation of severe or chronic disease. This unbalanced sample accumulation may accelerate research of some cohorts, but also may limit study of relatively benign conditions and the accrual of unaffected and unbiased control samples. BioVU represents a feasible model for pediatric DNA biobanking but involves both ethical and practical considerations specific to the pediatric population.